THE OPTIMATION SIMULTANEUOS DETERMINATION OF LEAD(II) AND CADMIUM(II) BY ADSORPTIVE STRIPPING VOLTAMMETRY (ADSV) - Deswati -; Hamzar Suyani; Umiati Loekman; Nilam Sari (Jurnal Riset Kimia, 2012)
A selective and sensitive adsorptive stripping voltammetric (AdSV) method for simultaneous determination of lead(II) and cadmium(II) were proposed. The aim of this study was to get the optimum condition for simultaneuos determination of lead(II) and cadmium(II). The parameters were studied such as: variation of accumulation potential, accumulation time, pH, and variation ofcalcon concentration. In this case, the optimum conditions were reached at accumulation potential –0.7 V, accumulation time 80 s, concentration of 0.12 mM calcon, and pH 7.0. At the optimumconditions the relative standard deviation were 2.90% and 1.46% for Pb(II) and Cd(II) respectively for eight replicates (n = 8) measurements. The method was applied for the direct determination of Pb(II) and Cd(II) in sea water around Bungus, Padang City. Concentration Pb(II) and Cd(II) insample were 9.918 μg/L – 27.320 μg/L for Pb(II) and 7.997 μg/L - 32.521 μg/L for Cd(II), with recovery of 99.48%, and 103.28 for Pb(II), and Cd(II) respectively.